2017
DOI: 10.3847/1538-4357/aa63f5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Optical Classification for Fermi Blazar Candidates with a Statistical Method Using Broadband Spectral Indices

Abstract: We aim to test if a blazar candidate of uncertain-type (BCU) in the third Fermi active galactic nuclei catalog (3LAC) can be potentially classified as a BL Lac object or a flat spectrum radio quasar (FSRQ) by performing a statistical analysis of its broadband spectral properties. We find that 34% of the radioselected BCUs (583 BCUs) are BL Lac-like and 20% of them are FSRQ-like, which maybe within 90% level of confidence. Similarly, 77.3% of the X-ray selected BCUs (176 BCUs) are evaluated as BL Lac-like and 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…We then compared our 120 identified BL Lac candidates with some other recent studies. We found that our results are mostly consistent with previous works presented in Chiaro et al (2016); Lefaucheur & Pita (2017); Yi et al (2017) and Kang et al (2019a) which utilize different statistical (e.g., SML) algorithms (see Table 4 and Table 3). The exceptions are as follows: 2 sources do not find matching sources and 2 sources did not provide a clear classification in Lefaucheur & Pita (2017).…”
Section: Comparison With Literature Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We then compared our 120 identified BL Lac candidates with some other recent studies. We found that our results are mostly consistent with previous works presented in Chiaro et al (2016); Lefaucheur & Pita (2017); Yi et al (2017) and Kang et al (2019a) which utilize different statistical (e.g., SML) algorithms (see Table 4 and Table 3). The exceptions are as follows: 2 sources do not find matching sources and 2 sources did not provide a clear classification in Lefaucheur & Pita (2017).…”
Section: Comparison With Literature Resultssupporting
confidence: 91%
“…There are an extra 55 BCUs (obtained easily from the the 3LAC Website version) with a misjudged rate η = 10/414 ≃ 2.415% (see Table 5) in the range (logVI < 1.702 and logF R < 2.258) in the logF R − logVI panel (the upper panel of right column in Figure 1). These sources (57, 22 and 55) have a larger misjudged rate (η > 2.4%); although we did not conclusively evaluate their potential classifications (FSRQs and BL Lacs), it may be helpful for source selection in the spectroscopic observation campaigns in the future to further diagnose their optical classifications (see e.g., Yi et al 2017;Massaro et al 2013 for the some discussions). In addition, if only one parameter is considered, a bigger misjudged error is introduced (see Table 5).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Supervised machine learning (SML) is a useful and alternative classification method and it provide reference for classification results. SML had been used by many scholars (Ackermann et al 2012;Chiaro et al 2016;Saz Parkinson et al 2016;Salvetti et al 2017;Lefaucheur & Pita 2017;Yi et al 2017;Kovačević et al 2019Kovačević et al , 2020Kang et al 2019a;Xu et al 2020;Xiao et al 2020;Zhu et al 2021b;Coronado-Blázquez 2022) to classify BCUs from the Fermi-LAT catalogs.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the BCUs is interesting and it can provide more sources for us to investigate the different physics in BL Lacs and FSRQs. The identifications of BCUs were carried out in many works [9,[25][26][27][28][29][30][31][32][33][34] In this work, we apply the support vector machine (SVM) learning method to separate BL Lacs and FSRQs and then use the dividing line to tell BL Lac candidates from FSRQ candidates from the BCUs. The work is arranged as follows: In the 2nd section, a sample, from 4FGL_DR3, used in the work will be described, in 3rd section the distributions of the physical parameters will be given for BL Lacs and FSRQs, and the SVM method will be used to separate BL Lacs and FSRQs, and divide BL Lac candidates and FSRQ candidates, some discussions and conclusions are given in section 4 and section 5.…”
Section: Introductionmentioning
confidence: 99%